The importance of clinical dental examination in the prevention of colorectal cancer: a case report - Fraga, Larissa Sandes; de-Freitas, Paulo Henrique Luiz; Valadares-Souza, Carolina Vieira; Souza, Gustavo Almeida (Journal of Oral Diagnosis, 2020)
The clinical dental examination has a great importance to establish diagnosis and treatment plan, besides that, for a well-trained dentist, can be an important tool to discover serious diseases in other organs and systems, for example Gardner’s Syndrome (GS). This Syndrome is a rare and hereditary disease, characterized by familial colorectal polyposis. Other alterations are epidermoid cysts, osteomas, odontomas may be present in this syndrome. The precocious diagnose of the disease its important, because the colorectal polyposis have a high malignant potential. This paper aims to report a case of GS diagnosed after a routine dental appointment. A 23-year-old female patient was attended at a public university in Brazil and reported hardened nodules in the mandible. In the radiographic exam, circumscribed radiopaque images suggestive of multiple osteomas were observed in the jaws. In addition, the patient had reported a family history of colorectal cancer and removal of an epidermoid cyst in her leg 5 years ago. The patient was referred to the university’s Coloproctology department, where colonic polyposis was found after colonoscopy. The histopathological reported adenoma, without signs of malignancy. The present work demonstrated that an accurate dental clinical examination can be a tool to assist the dentist in the discovery of serious diseases in organs and systems unrelated to his area of expertise.